Perancangan Aplikasi Penyandian Pesan Teks dengan Menggunakan Algoritma Digraph Cipher - Yhopi Suhelna (JUKI : Jurnal Komputer dan Informatika, 2020)
Humans interact with fellow humans using communication. Not everything that is communicated contains a message so that it can be known by many people, sometimes the communication is confidential so that only certain people can know it. The occurrence of data tapping submitted is certainly a problem if the data is confidential, therefore a data security system is needed so that the data cannot be stolen or changed by tappers or crackers. One solution to secure data is to use cryptography. Cryptography is the science and art of maintaining message security when messages are sent from one media to another without experiencing interference from third parties. Through cryptographic techniques, data can be changed into passwords that are not understood and return them back to the original, this process is called data encryption and decryption. This data security process uses the Digraph Cipher method. Some facilities in the Digraph Cipher method are the keys used in the encryption and decryption process are the same (symmetrical) and the decryption process is the opposite of the encryption process.